Research on electromagnetic relay forwarding bidirectional transmission technology while drilling - LI Shiyin; ZHANG Bowen; ZHANG Guanjie; ZHANG Zhi; QI Huayan; WANG Bo (Tongxin xuebao)
To solve the issues of unidirectional transmission, poor reliability, and low transmission rate in domestic drilling systems, a relay-based bidirectional electromagnetic transmission solution while drilling was proposed. Through field measurements of drilling transmission signals, the channel characteristics of wireless transmission through drill rods were depicted. A relay-based bidirectional communication protocol was designed, effectively enhancing the transmission distance and stability of drilling signals. A drilling prototype, composed of field programmable gate array (FPGA), amplification circuit, analog-to-digital converter (ADC), digital-to-analog converter (DAC), and antenna, was constructed and tested. Field test results demonstrate that the proposed scheme achieves reliable relay-assisted bidirectional transmission of electromagnetic signals, with a single-hop transmission distance of 30 m and relay transmission distance exceeding 100 m. Concurrently, the transmission rate of this scheme is at the kbit/s level, an order of magnitude improvement over traditional unidirectional drilling systems.